Pesona Outfit Sebagai Identitas Anak Muda Saat Mengunjungi Kafe - Rolika Firinanda; Shelaisha Ayu Citra Lestari; Ajeng Nurul Izzah; Maria Laras Pramesti (Lembaga Pengembangan Kinerja Dosen, 2023)
Cafe is identically known as a comfortable place to enjoy favorite beverages and food. But from time to time, it was more than that. Cafe evolved into a base camp for young people. It is redefined as a place that 'must go' by young people who are trendy and up to date. Not only that, OOTD are also considered. There will always be a qualification of what to wear in the cafe to look good, neat, and trendy. That shows the process of self branding. This research focused on how young people try to branding themselves both in cafe and media and how those influence their consumer actions. Analyze it using the Consumerism Theory by Jean Baudrillard, with a qualitative approach. The result shows that social media plays a significant role in young people's consumption behavior for self-branding needs. It told them how to live in this era and what their needs were. And those additional needs ultimately increase their spending.